Ranging Energy Optimization for a TDOA-Based Distributed Robust Sensor Positioning System. (6th December 2010) - Wang, Tao
Abstract : The author proposes a distributed localization scheme for an asynchronous wireless sensor network (WSN) consisting of at least two beacons as well as some anchors, each collaborating with the beacons to help the sensors within the corresponding service area for self-localization. Most interestingly, each sensor does not need to emit either ranging or communication signals to neighbor sensors in the proposed scheme. Instead, each sensor only needs to estimate the time-of-arrivals (TOAs) of incoming ranging signals from the beacons and the anchors, and then the time-difference-of-arrival (TDOA) between the signal propagating from each beacon to the sensor and the one from that beacon to the sensor via an associated anchor is produced and converted to a range difference measurement at the sensor for self-localization. Assuming the location estimator adopted achieves the associated Cramér-Rao bounds (CRB), the localization performance at each sensor is derived and analyzed. When the system features robust sensor positioning (RSP) in that a prescribed accuracy requirement is fulfilled in all service areas of the anchors, the author considers ranging energy optimization problems related to the beacons and the anchors, and presents practical algorithms to solve them. The effectiveness of those algorithms is illustrated by numerical experiments.